VD_FINDINFO Décision / 2015 / 826 vom 11. November 2015 - VD Tribunal cantonal (2015)
DÉTENTION PROVISOIRE, RISQUE DE RÉCIDIVE, PROPORTIONNALITÉ, PSYCHOTHÉRAPIE | 221 al. 1 let. c CPP (CH), 228 al. 1 CPP (CH), 237 CPP (CH)